SOCIAL SUPPORT AND ACADEMIC RESILIENCE OF SELECTED HIGHER EDUCATION STUDENTS OF ROXAS CITY - Dayalo, Angelica Mae Banes (President University, 2025)
This study was conducted to determine the degree of social support and the level of academic resilience of selected higher education students of Roxas City. A random sample of 313 college students were chosen as respondents of the study. The researcher utilized a descriptive-correlational research design. A stratified random sampling was used to gather the data. A validated and reliability tested researcher-made questionnaire was used to gather the needed data from randomly selected respondents. Statistical tools used to analyze an interpret data were frequency count, percentage mean, t-test, analysis of variance and Pearson r. The findings of the study revealed that the studentsâ€™ social support was high, based on the data gathered, it is evident that Informational support has the lowest mean among social supports, while the academic resilience was very high. On the other hand, there was a significant difference in degree of social support when grouped according to sex, type of higher education and type of student.Â In the level of academic resilience, there was a significant difference when grouped according to type of higher education and type of student. The findings recommend that in order to meet the particular needs of the college students, evaluation and assessment of various student profiles should be implemented before transforming to creative and productive career-related programs and counseling services to strengthen the individual needs of the college students.